2017
DOI: 10.1021/acs.analchem.7b02610
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Secondary Structure Changes in Calmodulin Using 2D-IR Spectroscopy

Abstract: Revealing the details of biomolecular processes in solution needs tools that can monitor structural dynamics over a range of time and length scales. We assess the ability of 2D-IR spectroscopy in combination with multivariate data analysis to quantify changes in secondary structure of the multifunctional calcium-binding messenger protein Calmodulin (CaM) as a function of temperature and Ca concentration. Our approach produced quantitative agreement with circular dichroism (CD) spectroscopy in detecting the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 79 publications
(169 reference statements)
2
52
0
Order By: Relevance
“…In principle, 2D-IR offers the scope to go beyond the AGR measurement by virtue of the information-rich 2D lineshape of the proteins, which gives the opportunity to resolve more than albumin and the γ-globulins 4. The major protein constituent of the γ-globulins is IgG (80%).…”
Section: Resultsmentioning
confidence: 99%
“…In principle, 2D-IR offers the scope to go beyond the AGR measurement by virtue of the information-rich 2D lineshape of the proteins, which gives the opportunity to resolve more than albumin and the γ-globulins 4. The major protein constituent of the γ-globulins is IgG (80%).…”
Section: Resultsmentioning
confidence: 99%
“…2D-IR spectroscopy 2D-IR spectroscopy has been used to probe the molecular vibrations of many systems including biological molecules and solvents and has provided visualisations of conformational structural changes and dynamics of molecules [25,29,[112][113][114][115][116][117][118][119][120]. Proof of principle studies have shown the power and sensitivity of 2D-IR as it observes molecular structures and changes within a system allowing identification of proteins, ligands, DNA and other markers, and it has the potential to aid in disease diagnosis [11,29,113,116,[120][121][122][123][124][125]. However the use of 2D-IR to study biofluids is in its infancy and requires development which faces many challenges.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…PCA has been shown to be a powerful tool for use with 2D-IR spectroscopy and has enabled extraction of information from 2D-IR datasets [23,29,122]. It is important to note that prior to fit using a bilinear model such as PCA, the data must be first altered into a suitable format, ideally where each 2D matrix is reshaped into a single dimensional vector.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…1, 4-11 As drug design turns towards therapeutic molecules that target dynamic protein structures, such time resolved insight may become a powerful tool. 26 In such cases, the ability to measure changes in structure, often affecting a small fraction of the overall protein Please do not adjust margins Please do not adjust margins molecule, may become important. With this in mind, several 2D-IR studies have assessed the ability to identify, categorise and measure protein structures.…”
Section: Protein Structure Determinationmentioning
confidence: 99%
“…It is thus important that 2D-IR has been shown to provide similar accuracy in terms of quantification of secondary structure, with a study of the Ca 2+ binding transition of calmodulin showing that 2D-IR spectroscopy is sensitive to a secondary structure change affecting just seven residues of the 150 residue protein. 26 Thus far, we have focused on 2D-IR experiments using broadband, short duration infrared pulses as the source of the excitation and detection pulses. However, a second, less widely used 2D-IR method called electron-vibration-vibration (EVV) 2D-IR has been applied to protein structure determination.…”
Section: Protein Structure Determinationmentioning
confidence: 99%